Accumulated oxygen deficit measurements during and after high-intensity exercise in trained male and female adolescents - Naughton, G. A.; Charlson, J. S.; Buffifant, D. C.; Selig, S. E.; Meldrum, K.; McKenna, M. J.; Snow, R. J. (European Journal of Applied Physiology, 1997)
The purpose of this study was to compare accumulated oxygen deficits and markers of anaerobic metabolism [plasma ammonia (NH 3) and lactate (La -) concentrations] in anaerobically trained male [n?=?8, age 14.8 (0.5) years; maximal oxygen consumption V?O 2 max 61.74 (2.23) ml?·? kg -1?· min -1] and female [ n?=?8, age 14.5 (0.2) years; V?O 2 max 49.62 (3.52) ml?·?kg -1?·?min -1] adolescents. The exercise protocol consisted of runs to exhaustion at speeds predicted to represent 120% and 130% of V?O 2 max. Arterialised blood samples were obtained from a pre-warmed hand via a catheter inserted into a forearm vein. Samples were taken at rest and after 1, 3, 5, 7, 10, 15 and 20 min of recovery. The high-intensity exercise resulted in mean accumulated oxygen deficits that were less ( P?-1) than in males (68.6?ml?·?kg -1). Lower ( P?3 and La -1, and a higher pH were evident in females compared with males during various stages of the 20-min recovery period. The increase in anaerobic performance in the male adolescent athletes when compared with their female counterparts was associated with an increased plasma concentration of selected plasma and blood metabolites. The observed results may reflect well-established differences between the sexes in the morphology and metabolic power of muscle.